Diatoms from Southwest Greenland. - Foged, Niels (Meddelelser om Grønland, 1973)
In material collected in 195? and 19?0 in localities situated between 59° 44' N and 61 °22'N in SW Greenland a total of 465 oligohalobous diatoms and 260 mesohalobous and polyhalobous diatoms is shown, 4 nov. var. and 4 nov. fo. included. A great number of the species and their varieties are not previously shown in Greenland. Chemical analyses of 31 water samples are given. 439 photos of 284 different diatoms {193 oligohalobous and 91 mesohalobous or polyhalobous forms) are reproduced in 29 plates.